“Third Parties” and Democracy 2.0 - Sirota, Léonid (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2015)
Although the Supreme Court of Canada has described freedom of political, and especially electoral, debate as the most important aspect of the protection of freedom of expression in Canada, no debate in Canadian society is so regulated as that which takes place during an electoral campaign. Parliament has set up—and the Supreme Court has embraced—an “egalitarian model” of elections, under which the amount of money participants in that debate can spend to make their views heard is strictly limited. “Third parties”―those participants in pre-electoral debate who are neither political parties nor candidates for office―are subject to especially strict expense limits. In addition to limiting the role of money in politics, this regulatory approach was intended to put political parties front and centre at election time. This article argues that changes since the development of the “egalitarian model” have undermined the assumptions behind it and necessitate its re-examination. On the one hand, since the 1970s, political parties have been increasingly abandoning their role as essential suppliers in the marketplace of ideas to the actors of civil society, such as NGOs, unions, and social movements. On the other hand, over the last few years, the development of new communication technologies and business models associated with “Web 2.0” has allowed those who wish to take part in pre-electoral debate to do so at minimal or no cost. This separation of spending and speech means that the current framework for regulating the pre-electoral participation of third parties is no longer sufficient to maintain political parties’ privileged position in pre-electoral debate. While the current regulatory framework may still have benefits in limiting (the appearance of) corruption that can result from the excessive influence of money on the political process, any attempts to expand it to limit the online participation of third parties must be resisted.